QT Interval Prolongation Is a Novel Predictor of 1-Year Mortality in Patients With COVID-19 Infection - Banai, Ariel; Szekely, Yishay; Lupu, Lior; Borohovitz, Ariel; Levi, Erez; Ghantous, Eihab; Taieb, Philippe; Hochstadt, Aviram; Banai, Shmuel; Topilsky, Yan; Chorin, Ehud (Frontiers in Cardiovascular Medicine, 2022)
Background: QT interval prolongation is common in critically ill patients and is associated with increased mortality. However, the predictive value of a prolonged corrected QT interval (QTc) for myocardial injury and long-term mortality among patients hospitalized with COVID-19 infection is not well known. Purpose: To evaluate the association of prolonged QTc with myocardial injury and with 1-year mortality among patients hospitalized with COVID-19 infection. Methods: A total of 335 consecutive patients hospitalized with COVID-19 infection were prospectively studied. All patients underwent a comprehensive echocardiographic evaluation within 48 hours from admission. Using the Bazett formula, the QTc interval was calculated from the first ECG tracing recorded at the ER. QTc ≥440 msec in males and ≥450 msec in females was considered prolonged. Patients with elevated cardiac biomarkers and/or echocardiographic signs of myocardial dysfunction were considered to have myocardial injury. The predictive value of QTc prolongation for myocardial injury was calculated using a multivariate binary regression model. One-year mortality rate of patients with and without QTc prolongation was compared using the log-rank test, and a multivariate Cox regression model adjusting for multiple covariates was performed to evaluate the 1-year mortality risk. Results: One-hundred and nine (32.5%) patients had a prolonged QTc. Compared to patients without QTc prolongation, patients with prolonged QTc were older (70±14.4 vs 62.7±16.6, p <0.001), had more comorbidities, and presented with a more severe disease. Prolonged QTc was an independent predictor for severe or critical disease (adjusted HR 2.14, 95% CI 1.3-3.5; p=0.002) and myocardial injury (adjusted HR 2.07, 95% CI 1.22-3.5; p=0.007). One-year mortality of patients with prolonged QTc was higher than those with no QTc prolongation (40.4% vs 15.5; p <0.001). Following adjustment to multiple covariates including myocardial injury and disease severity, QTc prolongation was found to be associated with increased 1-year mortality risk (HR 1.69, 95% CI 1.06-2.68, p=0.027). Conclusion: Prolonged QTc is associated with disease severity, myocardial injury and 1-year mortality among patients hospitalized with COVID-19 infection.